Women's experiences of outpatient induction of labour with double balloon catheter or prostaglandin pessary: A qualitative study. Issue 4 (July 2021) - Coates, Rose; Cupples, Georgina; Scamell, Amanda; McCourt, Christine; Bhide, Amarnath
Abstract: Background: One quarter to one third of women experience induction of labour. Outpatient induction of labour may be safe and effective but women's views of this setting and of different methods of induction are sparse. Aim: To explore women's experiences of outpatient induction of labour with either prostaglandin pessary or double balloon catheter. Methods: Qualitative study using semi-structured, audio-recorded interviews with twenty-one women recruited to a feasibility trial of outpatient induction of labour. Transcripts were coded and analysed using a thematic framework approach. Findings: Two key themes were identified. 'Ownership of induction of labour' concerned how women understood and experienced the induction of labour process and tried to maintain control of a procedure managed by medical professionals. Women felt unprepared for the steps in the process and for the time it would take. The balloon method was preferred as it was considered a gentler start to the process, although some women reported it was painful on insertion. 'Importance of place' reflected women's associations of the home with comfort, ease of support and distraction, and the hospital with safety yet also with discomfort and delays. Discussion: This sample of women were keen to start induction without hormones. The randomised controlled trial design may have biased the sample towards women who wanted to experience the balloon method and outpatient setting where these were not usually offered, thus further cohort studies would be beneficial. Conclusions: Women were positive about experiencing the early stages of induction of labour at home with the balloon catheter.